2020
DOI: 10.1016/j.ecolind.2019.106019
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Complexity Index to assess benthic biodiversity of a partially protected area in the southwest of the UK

Abstract: The soundscape of the marine environment is a relatively understudied area of ecology that has the potential to provide large amounts of information on biodiversity, reproductive behaviour, habitat selection, spawning and predator-prey interactions. Biodiversity is often visually assessed 2 | P a g e and used as a proxy for ecosystem health. Visual assessment using divers or remote video methods can be expensive, and limited to times of good weather and water visibility. Previous studies have concluded that ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 65 publications
0
12
0
Order By: Relevance
“…Technologies can increase the scope of data collection in marine environments ( Obura et al, 2019 ), but often require specialist training and equipment. Two promising visual and audio approaches amenable to rapid and community-level data collection for coral reef monitoring include (i) habitat metrics, such as rugosity, extracted from 3D models generated by photogrammetry (Structure from Motion SfM) ( Young et al, 2017 ; Burns et al, 2019 ) and (ii) use of acoustic indices as a proxy for vertebrate and invertebrate diversity ( Bertucci et al, 2016 ; Bohnenstiehl et al, 2018 ; Bolgan et al, 2018 ; Obura et al, 2019 ; Elise et al, 2019b ; Davies et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Technologies can increase the scope of data collection in marine environments ( Obura et al, 2019 ), but often require specialist training and equipment. Two promising visual and audio approaches amenable to rapid and community-level data collection for coral reef monitoring include (i) habitat metrics, such as rugosity, extracted from 3D models generated by photogrammetry (Structure from Motion SfM) ( Young et al, 2017 ; Burns et al, 2019 ) and (ii) use of acoustic indices as a proxy for vertebrate and invertebrate diversity ( Bertucci et al, 2016 ; Bohnenstiehl et al, 2018 ; Bolgan et al, 2018 ; Obura et al, 2019 ; Elise et al, 2019b ; Davies et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Replicate deployments were spaced ~100 m apart to depths ranging from 15 to 32 m, before being recovered after 45 min. Videos from BRUVs were assessed in situ to ensure that the camera had landed and recorded a viable sample (Davies et al, 2020; Davies, Holmes, Rees, et al, 2021). Failed attempts were repeated to ensure that all samples were suitable.…”
Section: Methodsmentioning
confidence: 99%
“…Sessile and sedentary epifauna were monitored using a towed underwater video system (“towed flying array” henceforth), while mobile species were monitored with Baited Remote Underwater Video systems (BRUVs; Davies et al, 2020; Davies, Holmes, Rees, et al, 2021; Sheehan et al, 2010; Sheehan, Stevens, et al, 2013; Sheehan et al, 2016; Stevens et al, 2014). The combination of these data collection methods, which estimate the abundance of species ranging from sessile branching sponges to highly mobile elasmobranchs, allow the assessment of a large proportion of the benthic ecosystem.…”
Section: Introductionmentioning
confidence: 99%
“…There are no depth or substrate limitations when using acoustic survey equipment allowing for large areas of Chapter 1: Challenges of assessing coastal environments: A review substrata to be mapped in a short space of time (Magorrian et al, 2009). Additionally, the use of acoustic measures such as the acoustic complexity index can be used to correlate with visual biodiversity estimates to offer an alternative to assess ecosystem health (Davies et al, 2020).…”
Section: Advantagesmentioning
confidence: 99%
“…Unlike underwater camera surveys, acoustic methods are not restricted by poor water visibility (Davies et al, 2020) whether it's for marine mammal and fish detection or benthic habitat mapping (Dudzinski et al, 2011). However, research has suggested that acoustic detections of organisms are susceptible to acoustic backscatter in areas of extreme turbulence or turbid sediment-laden waters (Melvin & Cochrane, 2014).…”
Section: Advantagesmentioning
confidence: 99%